Traumatic events and tonic immobility - Bados, Arturo; Toribio, Lidia; García-grau, Eugeni (The Spanish Journal of Psychology, 2008)
Tonic immobility is a basic defense strategy which has not been studied in depth in humans. Data suggest that it may be a relatively frequent phenomenon in victims of rape and sexual abuse, but its occurrence has not been systematically explored in other types of trauma. We carried out a retrospective study in a sample of 100 university students to establish whether tonic immobility varies depending on the nature of the worst trauma experienced, defined subjectively by each participant. Immobility was assessed using the Tonic Immobility Scale and traumas were assessed using the modified Traumatic Events Questionnaire. Seventy percent of the sample had experienced trauma of some kind. There were no significant differences in tonic immobility between different types of trauma (e.g., physical abuse, assault or aggression, serious accident), except that the mean tonic immobility score was significantly higher in the group with trauma due to physical/psychological or sexual abuse than in the group with trauma due to receiving news of the mutilation, serious injury, or violent or sudden death of a loved one. We conclude tentatively that tonic immobility may be typical not only of sexual traumas, but of other kinds of directly experienced traumas as well.